A Novel Risk Model Identified Based on Pyroptosis-Related lncRNA Predicts Overall Survival and Associates With the Immune Landscape of GC Patients - Xu, Tingting; Gu, Hanxin; Zhang, Changsong; Zhang, Wushuang; Liang, Xiaolong; Cheng, Xiaoxia (Frontiers in Genetics, 2022)
Gastric cancer (GC) is the most common malignant gastrointestinal tumor worldwide. Pyroptosis was widely reported to exert a crucial function in tumor development. In addition, pyroptosis was also proved to be associated with immune landscape. However, whether pyroptosis-related lncRNAs are associated with the prognosis and immune landscape of GC remains unclear. In the present study, we first constructed a novel risk model by using pyroptosis-related lncRNAs which could be utilized to predict the survival outcome and immune landscape of GC patients. We identified 11 pyroptosis-related lncRNAs for the establishment of the risk model. The results of survival analysis and AUC value of a time related ROC curve proved our risk model has an elevated efficiency and accuracy in predicting patients’ survival outcome. We also found that the risk model was also associated with the immune landscape, drug sensitivity and tumor mutation burden of GC patients. In conclusion, our risk model plays a crucial role in tumor immune microenvironment and could be used to predict survival outcome of GC patients.